E-Commerce, Ethical Commerce? - Maury, Mary D. (Journal of business ethics, 2002)
In this paper, we look at the new frontier of e-commerce, the ethical challenges it is facing and discuss some of the problems encountered and some of the solutions that are evolving. The areas of concern include the impact on other businesses, investors and consumers. Problems regarding financial reporting, intellectual property and privacy are discussed.